2017
DOI: 10.1209/0295-5075/120/38003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stock return distributions with a quantum harmonic oscillator

Abstract: We propose a quantum harmonic oscillator as a model for the market force which draws a stock return from short-run fluctuations to the long-run equilibrium. The stochastic equation governing our model is transformed into a Schrödinger equation, the solution of which features “quantized” eigenfunctions. Consequently, stock returns follow a mixed χ distribution, which describes Gaussian and non-Gaussian features. Analyzing the Financial Times Stock Exchange (FTSE) All Share Index, we demonstrate that our model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Economies 2021, 9, x FOR PEER REVIEW 9 of 16 quadrant of positive positions, which explains that returns are still moved. In this case, the high energy zone stands for the explanation of Bull market momentums (Ahn et al 2018;Ataullah et al 2008). Conversely, the fall of returns (Bear market momentum) is the negative quadrant-compared with the case of low energy with no evidence or information to push up.…”
Section: Quantum Mechanics and Wave Function For Time Series Movementmentioning
confidence: 92%
“…Economies 2021, 9, x FOR PEER REVIEW 9 of 16 quadrant of positive positions, which explains that returns are still moved. In this case, the high energy zone stands for the explanation of Bull market momentums (Ahn et al 2018;Ataullah et al 2008). Conversely, the fall of returns (Bear market momentum) is the negative quadrant-compared with the case of low energy with no evidence or information to push up.…”
Section: Quantum Mechanics and Wave Function For Time Series Movementmentioning
confidence: 92%
“…In the social version, the frequency can therefore be thought of as representing a linearised resistance to change. For something like a stock market, the frequency can be used to represent the speed of mean reversion of returns (Ahn et al, 2017), while the constant Z can be intepreted as a scaling factor.…”
Section: Question Order a Yes A No B Yes B Nomentioning
confidence: 99%
“…Another difference between quantum and classical oscillators is that the former features discrete energy levels. The ground state, which again can be viewed as representing the potential for a transaction to occur, corresponds to the normal distribution, while the other states show more complicated distributions, and contribute the non-normal behavior also seen with markets (Ahn et al, 2017).…”
Section: Question Order a Yes A No B Yes B Nomentioning
confidence: 99%
“…In fact, this has already been done. Ahn et al (2017) showed that a similar quantum oscillator model outperformed traditional stochastic process models for fitting historical price changes in the Financial Times Stock Exchange (FTSE) All-Share Index. The system was found to be in the ground state nearly all of the time, with the next two levels contributing the skewness and kurtosis that characterized the data.…”
Section: Quantum Oscillationsmentioning
confidence: 99%